2022
DOI: 10.1155/2022/1756266
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Its Impact on Perinatal Outcomes between Symptomatic and Asymptomatic Women

Abstract: Coronavirus disease 2019 (COVID-19) has been increasing among pregnant women worldwide. Its impact on maternal, fetal, and neonatal health is still scarce in the published literature. As a routine COVID-19 prenatal screening has been established for all women requiring hospitalization, it is not clear whether symptomatic women carry worse pregnancy outcomes than those without symptoms. We aimed to analyze perinatal outcomes between symptomatic and asymptomatic women admitted to our center. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
3
1
Order By: Relevance
“…3,24 In our study we observed significantly higher number of miscarriages in symptomatic pregnant women compared to asymptomatic; contradictory to a study conducted in Saudi Arabia, where rate of miscarriages did not significantly differ in symptomatic and asymptomatic Covid-19 pregnant women. 25 In the present study no difference was discerned regarding maternal age, gestational diabetes, parity, leukocyte count and platelet count in symptomatic and asymptomatic groups. Our study adds to currently available scanty data concerning COVID-19 infection in pregnant women in developing countries.…”
Section: Discussioncontrasting
confidence: 67%
“…3,24 In our study we observed significantly higher number of miscarriages in symptomatic pregnant women compared to asymptomatic; contradictory to a study conducted in Saudi Arabia, where rate of miscarriages did not significantly differ in symptomatic and asymptomatic Covid-19 pregnant women. 25 In the present study no difference was discerned regarding maternal age, gestational diabetes, parity, leukocyte count and platelet count in symptomatic and asymptomatic groups. Our study adds to currently available scanty data concerning COVID-19 infection in pregnant women in developing countries.…”
Section: Discussioncontrasting
confidence: 67%
“…Further data are needed to better understand how body weight and nutrition can influence the prognosis of COVID-19 in pregnancy, and how pre-pregnancy normalization of BMI and tailored nutritional supplementation can affect pregnancy outcomes [ 24 , 26 , 34 , 35 , 36 , 37 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roles for maternal age and COVID-19 severity in disease presentation and outcome of SARS-CoV-2 infected neonates is hotly disputed ( 1 , 3 , 32 , 33 ). Discordance is exemplified by 3 recent reviews that found a lack of “concrete” evidence for vertical transmission or adverse effects of SARS-CoV-2 infection on pregnancy or newborns ( 32 , 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Roles for maternal age and COVID-19 severity in disease presentation and outcome of SARS-CoV-2 infected neonates is hotly disputed ( 1 , 3 , 32 , 33 ). Discordance is exemplified by 3 recent reviews that found a lack of “concrete” evidence for vertical transmission or adverse effects of SARS-CoV-2 infection on pregnancy or newborns ( 32 , 34 , 35 ). Such discordance may be explained at least in part by an overriding majority of mildly symptomatic cases that differ only marginally from common complications of non-COVID pregnancies, and cases that were readily resolved by intensive care and anti-inflammation and/or antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%